Nanoencapsulation of nutraceuticals: enhancing stability and bioavailability in functional foods - Hao, Minglu; Tan, Xiaonan; Liu, Kang; Xin, Ning (Frontiers in Nutrition, 2026)
While nutraceuticals hold great promise for improving health, their efficacy is often limited by the poor stability and low bioavailability of many bioactive compounds. Nanoencapsulation has emerged as a transformative solution to these challenges, involving nanoscale carriers that protect sensitive nutrients from degradation and enhance their absorption. This review provides a comprehensive overview of nanoencapsulation strategies in the food and nutrition domain. We outline the historical development of key nanocarrier systems, from early liposomal delivery vehicles to advanced lipid nanoparticles, nanoemulsions, and biopolymer-based nanoparticles engineered for improved nutraceutical delivery. The physicochemical and biological mechanisms responsible for enhancing the performance of nanoencapsulation systems are systematically elucidated. Nanoencapsulation can shield bioactives from light, heat, oxidation, and pH extremes. It also improves oral bioavailability through enhanced solubility, controlled release, mucoadhesion, endocytosis-mediated uptake, and lymphatic transport that bypasses first-pass metabolism. Key examples of nanoencapsulated nutraceuticals in functional beverages, dairy products, dietary supplements, and other foods are highlighted, illustrating the growing commercial applications of food nanotechnology. We also discuss challenges related to manufacturing scale-up, safety and toxicology, regulatory oversight, and consumer acceptance of nano-enabled nutraceuticals, and we present emerging trends such as co-encapsulation of synergistic ingredients and precision nutrition approaches. By integrating advances in nanotechnology with nutritional science, nanoencapsulation is poised to significantly amplify the health benefits of functional foods and nutraceutical products in the coming years, paving the way for more effective functional diets and improved public health.